(untitled) (Global Journal of Science Frontier Research, 1969)
The extent of pollution of Imo, Utaewa Rivers and Essene Creek being sources of drinking water were assessed due to the smelting activities of the Aluminium Smelter at Ikot Abasi City, Nigeria. Soil and plants samples in the field near the water bodies were equally assessed. The physicochemical parameters investigated on all sampled water bodies were within the WHO and USEPA limits for drinking water with the exception of salinity, turbidity, TDS and few heavy metals (Mn, Fe, Al, Pb). The overall average levels of these parameters were 7.6±2.8 % (salinity), 16±12 FTU (Turbidity), 793±250 mg/L (TDS), 2.59±0.48 mg/L (Mn), 0.49±0.27 mg/L (Al) and 0.85±0.43 mg/L (Pb). Principal component biplot revealed strong and positive metal loadings whose ranges were (1.284-1.687), (0.499-0.515) and (0.959-1.630) for Essene Creek, Imo River and Utaewa River respectively. Similarly, clauster analysis showed that elemental compositions of soil and plants in the vicinity of aluminium smelter were traceable to the smelting activities. Also, accumulation of airborne particle by vegetation and surface soil was resulted from the activities in the smelting site. Al (1830 -2170 μg/g) and Zn (141-147 μg/g) were more abundant at 0-5 cm soil depth than other metals (Cd, Mn, Ni, Fe, Pb, Co). Bioccumulation results revealed increased metal uptake by Vernonia amygdalia (Bitter leaves), Manihot esculenta (Cassava) and Carica papaya (Paw-paw) at the sites closest to the industry, hence can be used as good biomarkers for soil pollution.